Hegemoni Kekuasaan Dalam Pemilihan Wacana Berita UU ITE Pada Website Kementrian Komunikasi dan Informasi - Arasta, Ghifary Muhamad; Sigit, Ridzky Rinanto (Magister of Communication Science, Sahid University Jakarta., 2021)
This research starts from the issue of press freedom in Indonesia and the rubber articles in the ITE Law, which can silence press freedom in Indonesia. Judging from the trend of attempts to criminalize journalists online using the rubber articles of the ITE Law in recent years. Instead of fixing and revising the rubber articles in the ITE Law, the Ministry of Communication and Information Technology is suspected of trying to dampen discourse on the revision of the ITE Law by collecting media news about the ITE Law, which is available on the kominfo.go.id website under the category 'media spotlight'. The purpose of this research is to understand the news discourse framing of the ITE Law in the 'media spotlight' category of the Kominfo website before and after the revision of the ITE Law is passed, as well as to reveal the framing used by the Ministry of Communication and Information as the hegemony of power in selecting of news discourse on the ITE Law on the Kominfo website. This research uses a critical paradigm, with a descriptive qualitative research approach using the analysis of the four functions of Entman framing and cascading network activation. The results showed that there were differences in the news framing of the ITE Law on the Kominfo website in the 'media spotlight' category. Hegemony was carried out to strengthen government dominance through its repressive tools, namely the ITE Law.